2010
DOI: 10.1002/qj.515
|View full text |Cite
|
Sign up to set email alerts
|

Airborne observations of the effect of a cold front on the aerosol particle size distribution and new particle formation

Abstract: Airborne measurements of condensation nuclei (CN), aerosol particles (APs) and sulphur dioxide (SO 2 ) were made near a cold front to examine new particle formation and the effects of the front on CN and SO 2 concentrations and the AP size distribution and concentration. Measurements were made in the boundary layer (BL) and free troposphere (FT) both preceding and following the passage of the front. Statistical analyses of CN and AP concentrations in the air masses around the front show that new particle forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…On the other hand, the particle mass concentration can be modified during long-range transport (e.g. Pio and Lopes 1998;Herrmann 2003;Bruckmann et al 2006;Peter et al 2010).…”
Section: Gravimetric Massmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the particle mass concentration can be modified during long-range transport (e.g. Pio and Lopes 1998;Herrmann 2003;Bruckmann et al 2006;Peter et al 2010).…”
Section: Gravimetric Massmentioning
confidence: 99%
“…Vecchi et al 2007;Brüggemann et al 2009;Katzman et al 2010;Lianou et al 2011) by transport (wind direction, precipitation), dilution (mixing height and wind velocity), the distribution between gas and condensed phase (temperature and humidity) and chemical composition resulting from chemical conversions (including gas phase, multiphase and heterogeneous reactions) (e.g. Herrmann 2003;Peter et al 2010;Hamed et al 2010;Mikkonen et al 2011). As a result, the physical and chemical properties of tropospheric particles at a rural site with urban influences should differ for different aerodynamic diameters (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Although solar radiation is likely the trigger for this nucleation event, other meteorological conditions may also influence the new particle formation process. For example, Peter et al (2010) reported enhanced NPF events associated with mixing between air masses of distinct thermodynamic properties, suggesting that large gradients in temperature and relative humidity may have promoted new particle formation via turbulent mixing. The regional nucleation event occurred after a persistent typical summer recir-culation pattern, with low pressure gradients over the western Mediterranean basin (19-22 September) and a second brief period (23-24 September) characterized by the advection of southern air from North Africa, with intrusion of Saharan Dust.…”
Section: Meteorological Parametersmentioning
confidence: 99%
“…Varying meteorological conditions influence these physical and chemical properties in a very complex manner (Vecchi et al 2007;Katzman et al 2010), while the chemical composition of the gas and particle phase is the result of chemical conversions by gas phase, multiphase and heterogeneous reactions (Herrmann 2003;Hamed et al 2010;Peter et al 2010).…”
Section: Introductionmentioning
confidence: 99%